Phytochemical screening and in vitro biological activities of Acmella paniculata flower and leaf extracts by citric acid monohydrate/glycerol deep eutectic solvent - Sivaraj, Rajina Shahmir (2025)
Subang nenek, scientifically known as Acmellapaniculata, is a flowering herb rich in various bioactive compounds. Traditionally, this plant has been conventionally extracted using organic solvents that are harmful to the environment. Recently, a green extraction method has used deep eutectic solvent (DES) as a solvent extractor. However, the potential of this extraction approach with DES requires further investigation. Therefore, the study aimed to characterise the physicochemical properties of a DES consisting of citric acid monohydrate, as the hydrogen bond acceptor (HBA) and glycerol, as the hydrogen bond donor (HBD) and to assess its efficiency through the phytochemical content and biological activities of A. paniculata flower and leaf extracts. The DES was created by mixing the HBA and HBD components, forming CA/Gly. The CA/Gly's physicochemical analysis included examination of functional groups, physical homogeneity, viscosity, pH, density, surface tension and solubility.